2017
DOI: 10.14336/ad.2017.0209
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Training are Varied and Occur in an Exercise Type-Dependent Manner in Elderly Men

Abstract: Regular exercise can decrease the deleterious effects of aging and limit the development and progression of chronic disease in elderly people, depending on the type, intensity, frequency, and duration of exercise. This study aimed to investigate the potential protective effects of different physical training programs on oxidative stress parameters and inflammatory and neurotrophic mediators in the serum of elderly men. Healthy male volunteers [60 to 80 years; n=55] were divided into four groups: control [Ctr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…After deleting duplicates, two reviewers (PTQ and RX) screened titles and abstracts and excluded unrelated records. Finally, 122 full-text articles were examined for eligibility, and 12 studies met the inclusion criteria (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Friedenreich et al, 2012; Irwin and Olmstead, 2012; Nishida et al, 2015; Abdollahpour et al, 2016; Alghadir et al, 2016; Conroy et al, 2016; Sbardelotto et al, 2017; Mohammadi et al, 2018). One of these 12 studies (Sbardelotto et al, 2017) was excluded, as data remained unavailable, despite attempts to contact the original author.…”
Section: Resultsmentioning
confidence: 99%
“…After deleting duplicates, two reviewers (PTQ and RX) screened titles and abstracts and excluded unrelated records. Finally, 122 full-text articles were examined for eligibility, and 12 studies met the inclusion criteria (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Friedenreich et al, 2012; Irwin and Olmstead, 2012; Nishida et al, 2015; Abdollahpour et al, 2016; Alghadir et al, 2016; Conroy et al, 2016; Sbardelotto et al, 2017; Mohammadi et al, 2018). One of these 12 studies (Sbardelotto et al, 2017) was excluded, as data remained unavailable, despite attempts to contact the original author.…”
Section: Resultsmentioning
confidence: 99%
“…Other reviews have reported that exercise training is generally effective for muscle strength and performance of healthy elderly adults regardless of training programs [ 45 - 47 ], while large clinical trials of exercise for individuals diagnosed with sarcopenia are still lacking. Compared with previous studies, our study has three strengths.…”
Section: Discussionmentioning
confidence: 99%
“…In the model-based human pose estimation method, the joint tree or other complex model of the human object is established first, and then, the parameters of human activity are obtained to realize the estimation of human pose. e preparation stage of model-based human pose estimation is to build a human model based on prior knowledge, so as to effectively constrain the feature change space, improve the computational efficiency, and further narrow the search range of matching [13].…”
Section: Human Pose Estimation Based Onmentioning
confidence: 99%